Agricultural Trade and Ultra-Poor in Pakistan: An Application of CGE Model. (December 2022) - Ahmad, Saud; Khan, Muhammad Aamir; Mustafa, Usman
In the modern integrated world, the synthesis of countries for trade is often viewed as a crucial source of income and growth disparities across nations. Well-known channels of economic theory can trace the growth effects of trade. However, there is a substantial conflict among empirical studies regarding gains from agricultural trade. Therefore, this study examines the economy-wide impact of agriculture trade liberalization/protection on agriculture production, agriculture trade, income redistribution and public welfare. An extension of the GTAP model known as MyGTAP is employed and the world economy is disaggregated into 20 regions and 11 sectors with Pakistan as a home country. Further, results explore greater gains from an increased level of liberalization towards the agriculture sector in terms of agriculture production, real factors' wage, terms of trade and household welfare. Rural households enjoy relatively higher real income and income inequality declines in Pakistan in the case of liberalization and protection. However, comparatively protectionism reduces inequality by the lower extent, and said study also points out that neither change in real gross domestic product nor public welfare turns out to be a good indicator of assessing potential impact of trade policies on income inequality.